2022
DOI: 10.14218/jcth.2022.00130
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Approach to Assessment of Liver Viability During Normothermic Machine Perfusion

Abstract: Liver transplantation is the most effective treatment of advanced liver disease, and the use of extended criteria donor organs has broadened the source of available livers. Although normothermic machine perfusion (NMP) has become a useful tool in liver transplantation, there are no consistent criteria that can be used to evaluate the viability of livers during NMP. This review summarizes the criteria, indicators, and methods used to evaluate liver viability during NMP. The shape, appearance, and hemodynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…By using normothermic machine perfusion, the percentage of grafts eligible for transplantation can be increased. This method allows real-time liver and bile duct function assessment and can predict short-term transplantation outcomes [111]. It has been suggested that using NMP after the initial SCS period facilitates the regeneration of impaired cellular metabolic processes [112].…”
Section: Perfusion Methods Considerationsmentioning
confidence: 99%
“…By using normothermic machine perfusion, the percentage of grafts eligible for transplantation can be increased. This method allows real-time liver and bile duct function assessment and can predict short-term transplantation outcomes [111]. It has been suggested that using NMP after the initial SCS period facilitates the regeneration of impaired cellular metabolic processes [112].…”
Section: Perfusion Methods Considerationsmentioning
confidence: 99%
“…All available machine perfusion devices allow for calculation of arterial and portal flows. Increased vascular resistance resulting in decreased arterial and portal flow may be an indicator of liver injury [22]. Decreased flow can also be consistent with the presence of fibrosis or cirrhosis or even macrosteatosis with secondary sinusoidal stenosis and reduced perfusion [23,24].…”
Section: Viability Assessmentmentioning
confidence: 99%
“…Decreased flow can also be consistent with the presence of fibrosis or cirrhosis or even macrosteatosis with secondary sinusoidal stenosis and reduced perfusion [23,24]. Several studies have included measures of liver perfusion as part of their viability criteria [12,22,25,26]. Although a specific value or cut-off for viability has not yet been determined, flows of more than 150 ml/ min for the hepatic artery and more than 500 ml/min for the portal vein have been proposed [16 & ].…”
Section: Viability Assessmentmentioning
confidence: 99%
See 2 more Smart Citations